Faster Steroid Cessation After Laser Interstitial Thermal Therapy Versus Medical Management in Biopsy-Proven Radiation Necrosis After Stereotactic Radiosurgery for Brain Metastasis: A Multicenter Retrospective Cohort Review. (16th November 2020) - Sankey, Eric W; Grabowski, Matthew M; Srinavasan, Ethan; Griffin, Andrew; Howell, Elizabeth P; Otvos, Balint; Tsvankin, Vadim; Atik, Ahmet; Johsi, Krishna; Barnett, Gene H; Fecci, Peter E; Mohammadi, Alireza M
Abstract: INTRODUCTION: Symptomatic radiation necrosis (RN) occurs in ∼9-14% of patients after stereotactic radiosurgery (SRS). Steroids are often required, with an inherent risk of steroid-induced morbidity. Laser interstitial thermal therapy (LITT) may be a meaningful alternative to prolonged steroid use. METHODS: Patients were restrospectively reviewed after medical-management (MM) or LITT for biopsy-proven RN. Patients were stratified by modality and assessed for time to steroid cessation and treatment failure. Treatment failure was defined as radiographic and clinical progression, necessitating a change in management. Sequential 1 × 1mm volumetric MRIs were obtained before and after treatment and imported into the BrainLab iPlan Cranial 3.0 software for quantitative, semi-automated volumetric analysis of contrast-enhancing (ceLV) and total lesion volume. RESULTS: Eighty-one patients, at an age of 58 (53-66) and baseline KPS of 80 (80-90) were assessed over 11.3 months (4.3-27.0). LITT was performed in fifty-seven (70%) patients. Baseline ceLV was 3.73 cm 3 (2.52-6.04) versus 4.94 cm 3 (3.24-7.19) for the LITT and MM groups, respectively (p>0.05). A significant decrease in ceLV was observed between scans at 0–2 months and 6–9 months in the LITT cohort (p = <0.01). Contrastingly, a significant decrease in ceLV was not observed in the MM group until after 12 months follow-up. An interval increase from baseline volume within the first 4 months after LITT was suggestive of progression. Treatment failure occurred in 13% of MM patients and 5% of LITT patients at 4.4 (4.1-5.3) and 4.0 (3.2-4.8) months, respectively (p>0.05). Steroid cessation occurred significantly faster in the LITT group (median 37 vs. 162 days, P = .0002). When controlled for age, preoperative enhancing volume, and post-operative seizure on multivariate analysis, patients were 3.2 times more likely to be weaned off steroids after LITT versus MM alone ( P = .0008). CONCLUSION: These data suggest that LITT for treatment of biopsy-proven RN significantly decreases time to steroid cessation, when controlling for other variables. In addition, an earlier response to treatment is generally observed in patients treated with LITT compared to MM. Large, prospective trials are needed to validate the utility of LITT for RN and its impact on steroid-induced morbidity.